Crystal structure of (E)-(3-(3-methylthiophen-2-yl)acryloyl)ferrocene, C18H16FeOS - Wang Yanjiao; Zheng Haoliang; Zhang Keyi; Li Xiaohua; Liu Bin (Zeitschrift für Kristallographie - New Crystal Structures)
C18H16FeOS, monoclinic, Cc (no. 6), a = 13.4809(7) Å, b = 13.3262(7) Å, c = 9.5652(6) Å, β = 120.604(2)°, V = 1479.02(15) Å3, Z = 4, Rgt(F) = 0.0364 wRref(F2) = 0.0882, T = 170 K.